2015
DOI: 10.3102/0162373714536608
|View full text |Cite
|
Sign up to set email alerts
|

Which Instructional Practices Most Help First-Grade Students With and Without Mathematics Difficulties?

Abstract: We used population-based, longitudinal data to investigate the relation between mathematics instructional practices used by 1st grade teachers in the U.S. and the mathematics achievement of their students. Factor analysis identified four types of instructional activities (i.e., teacher-directed, student-centered, manipulatives/calculators, movement/music) and eight types of specific skills taught (e.g., adding two-digit numbers). First-grade students were then classified into five groups on the basis of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 76 publications
5
50
1
3
Order By: Relevance
“…Specifically, the non-significant effect of language on early calculation performance and development is partially consistent with Morgan et al (2015)’s findings on effective mathematics instructions for young children with MD. Morgan et al (2015) found that for first graders with MD, compared to student-centered language-based activities (e.g., solving a math problem with a partner, peer tutoring, and explaining math), teacher-directed activities that focused on explicit and direct number knowledge instruction and practice showed a stronger correlation with students’ mathematics achievement. This finding, together with ours, suggests meaningful instruction in number with opportunities for practice (e.g., Frye, Baroody, Burchinal, Carver, Jordan, & McDowell, 2013; Lynn et al, 2013), not language-based student-centered activities, may more likely facilitate the improvement of calculations among at-risk young children.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Specifically, the non-significant effect of language on early calculation performance and development is partially consistent with Morgan et al (2015)’s findings on effective mathematics instructions for young children with MD. Morgan et al (2015) found that for first graders with MD, compared to student-centered language-based activities (e.g., solving a math problem with a partner, peer tutoring, and explaining math), teacher-directed activities that focused on explicit and direct number knowledge instruction and practice showed a stronger correlation with students’ mathematics achievement. This finding, together with ours, suggests meaningful instruction in number with opportunities for practice (e.g., Frye, Baroody, Burchinal, Carver, Jordan, & McDowell, 2013; Lynn et al, 2013), not language-based student-centered activities, may more likely facilitate the improvement of calculations among at-risk young children.…”
Section: Discussionsupporting
confidence: 78%
“…This is because in this case, we need to use a cross-classified model in HLM, which requires an even larger sample size. Thus, future work may look at whether teachers’ behavioral control or instructional approaches for at-risk children may help enhance the prediction of calculation development (Fuchs et al, 2005; Morgan, Farkas, & Maczuga, 2015). Lastly, we only included children with MDRD and most children in our sample came from low SES background.…”
Section: Discussionmentioning
confidence: 99%
“…These are small in the context of generally accepted conventions for interpreting ES yet are in a similar range or are somewhat above estimates reported in correlational studies of other factors considered malleable through school‐based interventions (e.g., classroom instructional practices, teacher quality, school climate, and degree of racial integration). For example, the estimated ES of differing classroom instructional practices on primary‐grade children's academic achievement are about .03 to .04 of a standard deviation (e.g., Morgan, Farkas, & Maczuga, ). We therefore interpret the predicted EF effect size magnitudes as nontrivial, particularly when considered within the limited set of factors known to be malleable through school‐based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that it is not clear how the guided play condition in the Ferrara et al (2011) study would compare to parent and child math talk during a formal math activity intended to teach spatial reasoning. As noted, formal learning activities may elicit the greatest amount of parent math guidance (e.g., Bjorklund et al, 2004), and such focused instruction in some instances may result in the greatest amount of child learning (Morgan, Farkas, & Maczuga, 2015). Indeed, a meta-analysis revealed an advantage of explicit instruction on learning compared to unguided activities.…”
Section: Structuring Math Activities In the Homementioning
confidence: 94%